A quick justification for business ethics - Lombardi, Louis G. (Journal of business ethics, 1985)
The article examines the question of whether business ethics courses ought to have an impact. Despite the still common attitude among students and some business professionals that ethical considerations are less pressing in business, I argue that moral obligations are just as important there as elsewhere. The emphasis on profits in business is related to other realms (e.g., hobbies and seeking and education) in which, though private goals are dominant, moral limits remain in force. Business ethics courses can play a crucial role in emphasizing the necessity of ethical analysis in business.